Utilization of university research findings for national development (2012)
Research is one of the hallmarks of University activities. As a result, numerous research findings and discoveries abound in a number of Universities in West Africa. Some of these findings are ground breaking while some are not necessarily so. The impact of a University must be felt within and outside its community. Apart from the production of man-power and the involvement of universities in community services, university findings in West Africa, like their counter-part in the developed world, ought to be utilized for national development. This is against the backdrop of existing practices where most university research findings and discoveries only end up in the University libraries. In the developed world, research findings play vital role in the socio-economic and political development of such nations. But same cannot be said of some African countries where research product and findings tend to be largely seen as only "academic exercise". But the developed world has gone a step further by utilizing academic resources from tertiary institutions in enhancing every aspect of their national life. The paper advocates a University- Stakeholders summits to address the issue of numerous research findings and discoveries, many of which are presently largely underutilized. Since a number of findings and discoveries are known to exist in most of these universities, they should be harnessed, processed, sieved and turned around for developmental activities in Africa and beyond.